Neuropsychological Testing in Interventional Cardiology Staff after Long-Term Exposure to Ionizing Radiation. (24th September 2015) - Marazziti, Donatella; Tomaiuolo, Francesco; Dell'Osso, Liliana; Demi, Virginia; Campana, Serena; Piccaluga, Emanuela; Guagliumi, Giulio; Conversano, Ciro; Baroni, Stefano; Andreassi, Maria Grazia; Picano, Eugenio
Abstract: This study aimed at comparing neuropsychological test scores in 83 cardiologists and nurses (exposed group, EG) working in the cardiac catheterization laboratory, and 83 control participants (non exposed group, nEG), to explore possible cognitive impairments. The neuropsychological assessment was carried out by means of a battery called "Esame Neuropsicologico Breve." EG participants showed significantly lower scores on the delayed recall, visual short-term memory, and semantic lexical access ability than the nEG ones. No dose response could be detected. EG participants showed lower memory and verbal fluency performances, as compared with nEG. These reduced skills suggest alterations of some left hemisphere structures that are more exposed to IR in interventional cardiology staff. On the basis of these findings, therefore, head protection would be a mandatory good practice to reduce effects of head exposure to ionizing radiation among invasive cardiology personnel (and among other exposed professionals). ( JINS, 2015, 21, 670–676)